The Eurasian security system and Belarus: problems of geopolitical interdependence - Laumulin, Murat T. (Journal of the Belarusian State University. International Relations, 2018)
This article identifies and considers the most important elements of the interdependence between the foreign policy of the Republic of Belarus and the process of formation and development of the Eurasian security system, including military-strategic cooperation between Belarus and Russia, development of the military-industrial complex, and the efforts of the CSTO to maintain security in Central Asia.